2011 IEEE 11th International Conference on Advanced Learning Technologies 2011
DOI: 10.1109/icalt.2011.128
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogy in Computer-Based Sport Training

Abstract: The central question addressed in this paper is the appropriate formal representation of learning outcomes in the motor skill domain so they can be interpreted and manipulated by computers as well as humans for the implementation of Computer-based Sport Training (CBST). Instructional design usually begins with the specification of behavioural objectives or intended learning outcomes. The field of educational psychology has long been sensitive to the desirability of establishing learning objectives for instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…And thus, the theory of feedback in the context of HCI is rather weak [27]. Furthermore, what makes it difficult is that feedback is of varying abstractions along different dimensions, ranging from low lexical level to a high semantic level, from a drill type of training to training more cognitive complex tasks in disperse application domains, ranging from Sports training [41] to Medical training [42] onwards to Pilot training [16]. This research has shown that it is possible to categorize data from a real-life exercise for use in designing a simulator.…”
Section: Resultsmentioning
confidence: 99%
“…And thus, the theory of feedback in the context of HCI is rather weak [27]. Furthermore, what makes it difficult is that feedback is of varying abstractions along different dimensions, ranging from low lexical level to a high semantic level, from a drill type of training to training more cognitive complex tasks in disperse application domains, ranging from Sports training [41] to Medical training [42] onwards to Pilot training [16]. This research has shown that it is possible to categorize data from a real-life exercise for use in designing a simulator.…”
Section: Resultsmentioning
confidence: 99%